BONDING ANALYSIS IN SOLID STATE COMPOUNDS: BORON CARBON OF RARE EARTH METALS - FADEL, L.; ZOUCHOUNE, F.; ZOUCHOUNE, B.; HALET, J-F.; SAILLARD, ET J-Y. (Courrier du Savoir; Vol. 3 (2003): Courrier du Savoir)
The combination of boron and carbon elements with rare earth metals leads to the formation of materials having interesting physical and structural properties. In theses compounds of formula MxByCz, The non-metal atoms form either two-dimensional networks, or mon-dimensional zig-zag chains, or finite linear units of various length. The dimensionality of boron-carbon sublattice is related to the average valence electron count (VEC) per light atom (B or C). The bonding properties of rare earth metal boron carbide compounds are analysed by means of extend Hückel tight-binding calculations. Results indicate that these compounds can be described in first approximation as being built of anionic units interacting with not fully oxidized metallic cations.